Perlindungan Hukum Terhadap Penanaman Modal Asing Pada Sektor Pertambangan Mineral dan Batubara di Indonesia: - - Vania Shafira Yuniar (Dialogia Iuridica, 2021)
One of the indicators of Indonesia's economic development is investors. Investors are actors who have a role to empower and manage potential resources to serve as the country's economic strength. Mineral and coal mining plays an important role in the national economy and has great potential in the development of the national economy. The purpose of this research is to determine and analyze about legal protection for foreign investment in the mineral and coal mining sector in Indonesia. The research method used in this article is normative legal research and through a literature study approach with secondary assessment of legal materials and juridical data analysis. The results of this study indicate that the regulations related to foreign investment in the mining sector still use Law Number 25 of 2007 concerning Investment and Law Number 3 of 2020 concerning Amendments to Law Number 4 of 2009 concerning Mineral and Coal Mining which are considered by the Government as a basic regulation that is still in accordance with current conditions in Indonesia regarding investment and mining of minerals and coal. Therefore, special arrangements are needed related to foreign investment in the mining sector, because the existing laws and regulations are unable to explain in detail the aspirations and needs of foreign investors in implementing cooperation contracts in mineral and coal mining activities.